Role of grain boundaries in hydrogen embrittlement of alloy 725: single and bi-crystal microcantilever bending study. (22nd March 2022) - Taji, Iman; Hajilou, Tarlan; Karimi, Shabnam; Schott, Florian; Plesiutschnig, Ernst; Barnoush, Afrooz; Johnsen, Roy
Abstract: In situ electrochemical microcantilever bending tests were conducted in this study to investigate the role of grain boundaries (GBs) in hydrogen embrittlement (HE) of Alloy 725. Specimens were prepared under three different heat treatment conditions and denoted as solution-annealed (SA), aged (AG) and over-aged (OA) samples. For single-crystal beams in an H-containing environment, all three heat-treated samples exhibited crack formation and propagation; however, crack propagation was more severe in the OA sample. The anodic extraction of H presented similar results as those under the H-free condition, indicating the reversibility of the H effect under the tested conditions. Bi-crystal micro-cantilevers bent under H-free and H-charged conditions revealed the significant role of the GB in the HE of the beams. The results indicated that the GB in the SA sample facilitated dislocation dissipation, whereas for the OA sample, it caused the retardation of crack propagation. For the AG sample, testing in an H-containing environment led to the formation of a sharp, severe crack along the GB path. Highlights: Single crystal (SC) and bi crystal (BC) in situ cantilever bending test is used. SC of over-aged sample experienced severe cracking than the aged sample. Load drop for SC over aged cantilevers occurs at lower distance than aged sample. Bi crystal cantilever of over-aged was more resistant than aged sample. Grain boundary in solution annealed cantilever mitigated the risk of embrittlement.